Sufficient Conditions and Applications for Carathéodory Functions - Neng Xu (Journal of Mathematics)
Let be the class of functions of the form which are analytic in . By using the method of differential subordinations, we give some sufficient conditions for Carathéodory function, that is, if satisfies and where , , , ,, then . Some useful consequences of this result are also given.